PENANGANGAN KAWASAN KUMUH DI BEBERAPA DAERAH DI JAWA DAN SUMATERA - Weldy Anugra Riawan (JURNAL PELITA KOTA, 2022)
The role of local governments in the sustainable development agenda has not yet fully achieved the 11th SDGS goal, which is to make cities and human settlements inclusive, safe, resilient, and sustainable. This study aims to formulate an out of the box strategy in responding to the 11 SDGS goals so that it can be achieved by Regional Governments in Indonesia using qualitative descriptive analysis methods based on primary and secondary data. The results of the study indicate that local government programs that must be encouraged in order to succeed in this goal are to facilitate sustainable natural resource management in slum and coastal settlements by protecting and improving ecosystems, encouraging disaster risk reduction/management, overcoming slums, thoroughly, community, institutional, collaboration, based on strategy formulation. Recommendations based on research results are: encourage programs that are characterized by "Tatap Pelangiku", which is a strong and safe community in residential areas through reforestation, sustainability, and collaboration efforts according to the NUA-SDGS agenda that is adaptive and not slum. Keywords: Role of Local Government; Slums; Resilience Settlements Abstrak Peran pemerintah daerah dalam agenda pembangunan berkelanjutan belum sepenuhnya dapat mencapai tujuan ke-11 SDGS, yaitu membuat kota dan pemukiman penduduk yang inklusif, aman, tangguh, dan berkelanjutan. Penelitian ini bertujuan untuk merumuskan strategi out of the box dalam mensikapi tujuan ke-11 SDGS agar dapat dicapai oleh Pemerintah Daerah di Indonesia yang menggunakan metoda analisis deskriptif kualitatif berbasis data sekunder. Hasil penelitian menunjukkan bahwa program Pemerintah Daerah yang harus didorong dalam rangka mensukseskan tujuan tersebut adalah memfasilitasi pengelolaan sumber daya alam berkelanjutan di permukiman kumuh dan pesisir dengan cara melindungi dan memperbaiki ekosistem, mendorong pengurangan/manajemen risiko bencana, mengatasi kumuh, tuntas, komunitas, kelembagaan, kolaborasi, berdasarkan rumusan strategi. Rekomendasi berdasarkan hasil penelitian yaitu: mendorong program yang bercirikan “tatap pelangiku”, yaitu komunitas tangguh dan aman pada kawasan permukiman melalui upaya penghijauan, berkelanjutan, serta kolaborasi sesuai agenda NUA-SDGS yang adaptif dan tidak kumuh. Kata Kunci: Peran Pemerintah Daerah; Daerah Kumuh; Permukiman Berketahanan